ISLAMIC WORKING ETHOS OF FISHERMEN COMMUNITY AT BAGAN KUALA VILLAGE, TANJUNG BERINGIN SUB-DISTRICT, SERDANG BEDAGAI REGENCY - Effendi Sadly (Universitas Islam Islam Sumatera Utara, 2018)
This study aims to explain how the working ethos of the fishermen community at Bagan Kuala village Tanjung Beringin sub-district Serdang Bedagai regency and the implementation of this working ethos in improving their welfare of life. This type of research is qualitative with the anthropological-naturalistic approach which is adopted from the theory of Symbolic Anthropology built by Clifford Geertz.it is used as the main theory to understand the symbolic phenomena of economic anthropology and social psychology and Islamic economic philosophy about working ethos of fishermen community at Bagan Kuala village, Tanjung Beringin sub-district, Serdang Bedagai regency. The result of this study is that the Islamic teachings are not totally applied among the fishermen community of Bagan Kuala village. This then causes the working ethos of the fishermen to become low. The working ethos in Islamic teachings is understood among them only as an effort to fulfill obligation only. There is no effort to increase the obligation as motivation of the working ethos in order to make the working ethos of them become higher. In attempting to improve the life welfare of the fishermen community at Bagan Kuala village, they must maintain the implementation of working ethos based on efficiently spending time, sincere intention, commitment on determination and belief, not easily giving up, and istiqamah. The implementation of working ethos is based on frugality life, efficiency and honest attitude.